Basics of Biblical Hebrew grammar - Pratico, Gary Davis; Van Pelt, Miles V., 1969- (Grand Rapids, MI. Zondervan Academic, 2019)
Basics of Biblical Hebrew Grammar is the standard textbook for colleges and seminaries. The third edition of Basics of Biblical Hebrew Grammar represents a significant updating and revision of the previous edition with the goal of providing students with the best possible tool for learning Biblical Hebrew. Some of the keys to the effectiveness of Basics of Biblical Hebrew Grammar in helping students learn is that it: Combines the best of inductive and deductive approaches; Uses actual examples from the Hebrew Old Testament rather than "made-up" illustrations; Emphasizes the structural pattern of the Hebrew language rather than rote memorization, resulting in a simple, enjoyable, and effective learning process; Employs colored text that highlights key features of nouns and verbs, allowing easy recognition of new forms; Includes appendices of verbal paradigms and diagnostics for fast reference and a complete vocabulary glossary; Displays larger font and text size, making reading easier. By the time students have worked their way through Basics of Biblical Hebrew Grammar they will have learned:The Hebrew Alphabet; Vocabulary for words occurring 70 times or more in the Hebrew Bible; The Hebrew noun system; The Hebrew verbal system; A robust suite of learning aids is available for purchase to be used alongside the textbook to help students excel in their studies. These include a workbook; video lectures for each chapter featuring the author; flashcards keyed to vocabulary in each chapter; a laminated study sheet with key concepts; audio of the vocabulary for each chapter to aid in acquisition; and a compact guide to help refresh students refresh their memory on language forms, grammar, and word meanings
The basics of Hebrew writing -- The basics of Hebrew nouns and nominals -- Introduction to Hebrew verbs and the Qal Stem -- Introduction to derived stems -- Readings and studying your Hebrew Bible.
The Third edtion is completely revised.
Includes bibliographical references and index.
Keywords: Bible. -- Language, style; Bible; Bible -- Language, style; Hebrew language -- Grammar; Hebrew language -- Grammar; Hebrew language, Biblical -- Grammar; Hebrew language, Biblical -- Grammar -- Textbooks for foreign speakers -- English; Problems and exercises